How does city group risk-taking affect climate-friendly technology innovation in cities? Evidence from China - Chen, Xiaohui; Zhang, Hongwei (Technological and Economic Development of Economy, 2025)
Climate-friendly technology innovation, which always comes with risk, is becoming an essential tool for Chinese cities to cope with climate change. As a macro variable, how does city group risk-taking affect climate-friendly innovation in cities? This study conducts a qualitative analysis on the basis of the theory of planned behaviour. Then, Chinese city data from 2008 to 2020 are employed to study the impact of city group risk-taking on climate-friendly technology innovation with city and year two-way fixed effects models. The results show: first, city group risk-taking promotes climate-friendly technology innovation in cities; for every one standard deviation increase in the level of city group risk-taking, the level of climate-friendly technology innovation in cities increases by 0.1294 standard deviations. Second, city group risk-taking improves a city’s market vitality and promotes the city’s governmental technology investments, both of which are conducive to climate-friendly technology innovation in cities. Third, the role of city group risk-taking in promoting climate-friendly technological innovation in cities is heterogeneous and is greater in cities with high enthusiasm for financial technology innovation, in cities with high population density and in cities with high environmental penalties. First published online 15 April 2024